Primary ovarian lymphoma: A case report - Charlotte Gerrity; Alyssa Mercadel; Abrar Alghamdi; Marilyn Huang (Elsevier, 2023)
While Non-Hodgkin Lymphoma (NHL) often involves the ovaries at time of autopsy, it is rarely present at the time of diagnosis. Here we present a case of a 20-year-old who presented with a large adnexal mass and elevated B-HCG, CA-125, and LDH. The patient underwent exploratory laparotomy, and frozen section of the left ovarian mass was suspected to be a dysgerminoma. Final pathologic diagnosis was Ann Arbor stage IVE Diffuse Large B-Cell Lymphoma, germinal center subtype. Patient is currently undergoing chemotherapy and has received the 3 of a planned 6 cycles of R-CHOP.